Intravenous granisetron attenuates hypotension during spinal anesthesia in cesarean delivery: A double-blind, prospective randomized controlled study - Ahmed A Eldaba; Yasser M Amr (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: This study was conducted to determine the effectiveness of intravenous (IV) granisetron in the prevention of hypotension and bradycardia during spinal anesthesia in cesarean delivery. Material and Methods: A total of 200 parturients scheduled for elective cesarean section were included in this study. They were randomly divided into two groups. Group I was given 1 mg granisetron diluted in 10 ml normal saline slowly IV, 5 min before spinal anesthesia. Group II was given 10 ml of normal saline, 5 min before spinal anesthesia. Mean arterial blood pressure and heart rate (HR) were recorded every 3 min until the end of surgery (for 45 min). The total consumption of vasopressors and atropine were recorded. Apgar scores at 1 and 5 min were also assessed. Results: Serial mean arterial blood pressure and HR values for 45 min after onset of spinal anesthesia were decreased significantly in group II, P < 0.0001. The incidence of hypotension after spinal anesthesia was 64% in group II and 3% in group I (P < 0.0001). The total doses of ephedrine (4.07 ± 3.87 mg vs 10.7 ± 8.9 mg, P < 0.0001), phenylephrine (0.0 microg vs 23.2 ± 55.1 microg, P < 0.0001), and atropine (0.0 mg vs 0.35 ± 0.49 mg P < 0.0001) consumed in both the groups respectively, were significantly less in group I versus group II. Conclusion: Premedication with 1 mg IV granisetron before spinal anesthesia in an elective cesarean section significantly reduces hypotension, bradycardia and vasopressors usage.